‘You’re Loseff?’ ‘No, lifshits am I’: self-naming in Lev Loseff’s Poetry - Красильникова, Татьяна (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The article is a part of a study titled “The Lyrical Character in Lev Loseff’s Poetry: Image, Name and Reflection”, concerned with three aspects: firstly, the category of “the lyrical character”, proposed to describe the author’s image in a substantial corpus of Loseff’s poems; secondly, the issue of self-naming; thirdly, the motive of the subject’s reflection in a mirror. In real life Loseff had a number of names and surnames and it is not surprising that their multiplicity found its way into his poetry. The perspective adopted in the article enables a better understanding of Loseff’s poetics as well as opens new areas for discussion.